La réécriture du mythe Simorgh dans « Tuez-les tous » de Salim Bachi The Rewriting of the SimorghMyth in « Kill Them All » by Salim Bachi - Belkacemi, Sarra (Milev Journal of Research and Studies, 2021)
The originality of Salim Bachi's writing comes from a real aesthetic quest that favors the rewriting of ancient myths and their insertion into modern narratives. The writer develops his project writing based on previous texts, and makes a choice among the facts that he wants to represent and models the original version of a myth by giving it a new breath, a new meaning. Thus, in “Kill them all”, the author was inspired by the mystical epic “The language of the birds” of the great Persian Sufi poet Farid-ud-Din 'Attar to stage a new figure of Sîmorgh that goes with his story of suicide bombing. Indeed, the author proceeds to a real deconstruction and a reconstruction of the original myth to give it a new significance. By this transformation, Salim Bachi gives birth to a modern Sîmorgh, not that of 'Attar who goes in search of his king but rather a new Sîmorgh which leads us to the attack of September 11, 2001.